Psychological Impact of the COVID-19 Pandemic on Frontline Health Care Workers During the Pandemic Surge in New York City. (January 2021) - Feingold, Jordyn H.; Peccoralo, Lauren; Chan, Chi C.; Kaplan, Carly A.; Kaye-Kauderer, Halley; Charney, Dennis; Verity, Jaclyn; Hurtado, Alicia; Burka, Larissa; Syed, Shumayl A.; Murrough, James W.; Feder, Adriana; et al.
Background: This study sought to assess the magnitude of and factors associated with mental health outcomes among frontline health care workers (FHCWs) providing care during the Spring 2020 COVID-19 pandemic surge in New York City. Methods: A cross-sectional, survey-based study over 4 weeks during the Spring 2020 pandemic surge was used to assess symptoms of COVID-19-related posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and generalized anxiety disorder (GAD) in 2, 579 FHCWs at the Mount Sinai Hospital. Participants were additionally asked about their occupational and personal exposures to COVID-19. Multivariable logistic regression and relative importance analyses were conducted to identify factors associated with these outcomes. Results: A total of 3, 360 of 6, 026 individuals completed the survey (55.8% participation), with 2, 579 (76.8%) analyzed based on endorsing frontline responsibilities and providing information related to the three outcomes. 1, 005 (39.0%) met criteria for symptoms of COVID-19-related PTSD, MDD, or GAD. 599 (23.3%) screened positively for PTSD symptoms, 683 (26.6%) for MDD symptoms, and 642 (25.0%) for GAD symptoms. Multivariable analyses revealed that past-year burnout was associated with the highest risk of developing symptoms for COVID-19-related PTSD (odds ratio [OR] = 2.10), MDD (OR = 2.83), and GAD (OR = 2.68). Higher perceived support from hospital leadership was associated with a lowest risk of all outcomes [PTSD (OR = 0.75), MDD (OR = 0.72), and GAD (OR = 0.76). Conclusion: In this large sample of FHCWs providing care during the 2020 NYC pandemic surge, 39% experienced symptoms of COVID-19-related PTSD, MDD, and/or GAD and pre-pandemic burnout as well as leadership support were identified as the most highly associated factors. These findings suggest that interventions aimed at reducing burnout and augmenting support from hospital leadership may be appropriate targets to mitigate the risk for developing further psychopathology in this population and others working in the midst of crisis.